Geoid and postglacial rebound related gravity change in Finland - Bilker-Koivula, Mirjam (Aalto University, 2021)
Defence is held on 23.4.2021 16:00 – 19:00 Remote: https://aalto.zoom.us/j/61678768590 Positioning using Global Navigation Satellite Systems (GNSS) is widely used nowadays and it is getting more and more accurate. This requires also better geoid models for the transformation between heights measured with GNSS and heights in the national height system. In Finland heights are continuously changing due to the Fennoscandian postglacial rebound. Land uplift models are developed for the Fennoscandian land uplift area, not only for the vertical velocities, but also for the gravity change related to postglacial rebound. In this dissertation geoid studies were carried out in search of the geoid model that is most suitable for the conversion of GNSS heights in the EUREF-FIN coordinate system to heights in the Finnish height system N2000 on land as well as on sea. In order to determine the relationship between gravity change rates and vertical velocities, time series of absolute gravity measurements were analysed. Methods were tested for fitting a geoid model to GNSS-levelling data. The best method for Finland was found to be least-squares collocation in combination with cross-validation. The result was the height conversion surface FIN2005N00, the official model for Finland. Then, high-resolution global gravity field models were tested in geoid modelling for Finland. The resulting geoid models were better than the earlier geoid models for Finland. After correcting for an offset and tilt, the differences with other models disappeared. Also, a method was developed to validate geoid models at sea using GNSS measurements collected on a vessel. The method was successful and key elements were identified for the process of reducing the GNSS observations from the height of observation down to the geoid surface. Possible offsets between different types of absolute gravimeters were investigated by looking at the results of international comparisons, bi-lateral comparisons and of trend calculations. The trend calculations revealed ...